Soliditas Partai Amanat Nasional (PAN) Kabupaten Merangin pada Pemilihan Kepala Daerah (Pilkada) Serentak 2024 dalam Prespektif Kepemimpinan Prosedural (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the solidity of the National Mandate Party (PAN) in Merangin Regency during the 2024 Simultaneous Local Elections, which unfolded amid notable political dynamics and differing preferences between the party’s central and regional structures. Party solidity is analyzed using Firman Noor’s theory of party solidity, focusing on procedural leadership represented by two key indicators: decision-making mechanisms and the role of charismatic leadership. The study aims to understand how these indicators influence PAN Merangin’s organizational stability throughout the process of determining political support. Using a qualitative case study approach, data were collected through in-depth interviews, documentation, and media reports, then analyzed using the Miles and Huberman interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that although PAN Merangin formally implemented decision-making procedures according to the party’s statutes (AD/ART), the practice remained dominated by top-down communication from the central board (DPP), limiting regional participation in strategic political decisions. Meanwhile, the charismatic leadership of the PAN Merangin Chairman played a crucial role in maintaining organizational cohesion, reducing internal tensions, and ensuring cadre loyalty to central decisions. These results suggest the need to strengthen two-way structural communication and enhance the capacity of local party leaders to reinforce party solidity in future political contests.